Implementation of e-filing system and Indonesian tax payer compliance (Lighthouse Publishing, 2023)
This study was conducted in six tax service offices located throughout Lampung, namely Metro pratama tax service office, Bandar Lampung One pratama tax service office, Bandar Lampung Dua pratama tax service office, Natar pratama tax service office, Kotabumi pratama tax service office, and the Pratama Tax Service Office. Bandar Lampung Madya tax services. The purpose of this study was to determine the relationship between perceived ease of use of e-filing and individual taxpayer compliance in submitting annual tax returns and the quality of the e-filing system. return. review of the impact of individual taxpayer compliance in submitting annual notifications of perceptions of understanding the use of e-filing. hide the impact of the security and confidentiality of the electronic filing system on individual taxpayer compliance in longing for annual tax returns. With the aim of changing the magnitude of the influence between the variables studied, quantitative analysis research methods are used for research on certain populations or samples, data collection is carried out using instrument research, and data analysis is quantitative or statistical in nature. 300 people participated in this study through cluster random sampling as the sampling method. The software in this study is smartPLS, and the partial least squares (PLS) method is used to analyze the data. Individual taxpayer compliance is positively influenced by system quality, perceived convenience, perceived understanding, confidentiality, and security in the e-filing system.